Plasma-Treated CVD Graphene Gas Sensor Performance in Environmental Condition: The Role of Defects on Sensitivity. (4th November 2019) - Capote Mastrapa, Gil; Freire, Fernando Lazaro
Abstract : In this work, a low-cost resistive gas sensor based on graphene grown by CVD was fabricated and its sensitivity was studied in terms of defect density. CVD graphene was transferred using Polyurethane as sacrifice layer with low contamination and defect-free results. An atmospheric plasma etching system was used to homogeneously induce defects on the sensor's active area, as investigated through Raman spectroscopy. Device sensing properties were significantly enhanced for greater defect density for both NH 3 and NO 2 . The modified sensors were submitted to different concentrations of both target gas to assess detection limits and overall behavior. It was revealed that defective CVD graphene devices possess sensitivity up to ppm range with linear dependence in the range of values measured. The fabricated sensors presented little to no signal degradation after months of atmospheric exposure.